Energy Transition in South Korea: Energy Democracy, Collaborative Governance or Conflict Expansion? - Kim, Dong Young (The Korean Association for Governance, 2020)
This paper explores and evaluates the evolution of energy governance for energy transition in Korea by focusing on national long-term energy planning since 1997 and on its potential impact on the long-term goals of the shares of nuclear energy and renewable energy in energy mix set by those plans. While governance for national long-term energy planning in Korea seems to have been democratized, energy governance has been very politicized and strategic according to political ideologies of administrations in ways to change or select decision-making venues and members of the participants. Such strategic political factors for governance seem to be instrumental in explaining fluctuations of the energy mix in various national long-term energy planning since 1997. Collaborative governance mode was adopted for energy governance during participatory government early 2000s but in vain. And, in general, Korean evolution of energy governance can be explained relatively well with conflict expansion mode rather than energy democratization mode that appears in European countries. Korean model of energy governance may have problematic consequences of lingering animosity and distrust among stakeholders and policy uncertainties that may affect firm’s investment decision negatively. 이 논문은 1997년 이후 한국의 장기적인 에너지 계획 수립을 위한 거버넌스 체계의 변화를 살펴봄으로써 한국의 에너지 전환을 위한 거버넌스의 특징을 발견하고 정책적 함의를 발견하고자 하였다. 에너지 전환 측면에서 원자력 에너지와 재생 에너지 간의 상호 경쟁적인 관계에서의 정치적 갈등에 초점을 맞추어 거버넌스 체계의 구체적인 변화가 에너지 전환에 어떻게 영향을 미칠 수 있는지 탐색해 보았다. 특히, 에너지 전환 또는 정책 변환에 관련된 세 가지 모델 (에너지 민주주의, 협력적 거버넌스, 갈등 확산)을 문헌연구에서 파악하여 한국의 거버넌스 특징과 비교해 보았다. 한국의 경우, 민주주의의 공고화로 인해 폐쇄적인 에너지 거버넌스가 점차 개방되고, 일반 시민들도 공론 조사 등을 통해 에너지 정책에 대한 숙의가 가능해 진 반면, 정치적 이념이 다른 정부가 집권하는 경우, 자신들의 이해관계에 유리하도록 거버넌스의 구조를 전략적으로 바꾸면서 정책을 결정하는 경향을 보임으로써 갈등이 확산되는 양상을 보이게 된다. 한국의 정부 주도 에너지 계획 모델은 의회와 시민 사회 주도인 독일의 에너지 민주주의 모델과 달리, 참여 정부 당시 시도되었던 협력적 거버넌스 모델의 실패 이후 갈등 확산 모델로 설명이 가능하며, 그 결과, 이해당사자간 불신과 갈등이 심화되고, 정치적 상황 변화에 따른 정책적 불확실성이 커지는 문제를 가지게 되었다.